Ethnomathematics present in dream filters in Mathematics classes in the Guarani de Ocoy indigenous land (Research, Society and Development, 2022)
This study presents some schools and students who study the research of a teaching research of students and apprehend a research of teaching for the students and the learning of the students São Miguel do Iguaçu, in the western region of Paraná. We look for elements of Ethnomathematics used in the creation and development of their students as symbologies, as well as everyday and cultural ones from the native manufacturing practices of the dissemination processes of this people. For this, we carry out activities with students from the Ocoy village. In an organizational exercise of this description, we seek to investigate the processes of generation, organization and transmission of knowledge through the bias of the Ethnomathematics program to present the people and their histories in the Guarani handicrafts. From this, we can infer that the knowledge present in the artisanal confections that the Guarani students of Ocoy dominate in the accomplishment of the represent a cultural sense and a social differential for this community. Thus, as possible useful tools for the integration, incorporation and construction of indigenous and non-indigenous mathematical knowledge, bringing them closer to the reality of this people.